PENGEMBANGAN MODEL PEMBELAJARAN KETERAMPILAN SOSIAL ANAK AUTIS DI TK B - Suharsiwi, Suharsiwi (JIV-Jurnal Ilmiah Visi, 2015)
This research aimed at developing the social skills of the children with autism in social interaction, communication and independence through social skills learning model, ACT-Me (Autism Children Teaching Model). The method used was the Research and Development (R and D), developed by Borg & Gall. The Model was developed in 2012-2014 at a number of schools in Jakarta, Tangerang and Depok. Stages of product development were done at a special school â€œMutiara Hati BSDâ€, limited testing phase was also conducted inclusively in â€œSekolah Semut-Semutâ€. The study founded that there is a great need of training teachers using this model as the results show that this model has been found effective in the field of testing. Besides, some suggestions were received from the experts to improve this model. Testing done on the effectiveness of the model showed, this model of learning social skills have eligibility of above 80%. The material used covers in the area of syllabus, daily planning, assessment, student workbook, and a number of media that can be applied in an inclusive and special schools. The research recommends to expand the areas of similar research so that the model can be applied all over Indonesia.